Teori Pemidanaan Diferensiasi (Special Treatment Theory) Untuk Anak Yang Berhadapan Dengan Hukum, Antara Balas Dendam Dan Penegakan Hak Asasi Manusia - Kesuma, Derry Angling; Hasyim, Rohman; Cayo, Putri Sari Nilam (Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
The development of the concept of punishment for children in conflict with the law in Indonesia through the Juvenile Criminal Justice System must prioritise a restorative justice approach, namely the settlement of criminal cases by involving the perpetrator, victim, families of the perpetrator/victim, and other related parties to jointly seek a fair settlement with an emphasis on restoration to the original situation, rather than retribution, including: criminal investigation and prosecution of children in accordance with the provisions of laws and regulations, unless otherwise specified in the Juvenile Criminal Justice System Law; juvenile trials by courts within the general court system; and guidance, supervision, and/or assistance during the criminal process or measures and after serving the sentence or measures. If diversion does not result in an agreement or the agreement cannot be implemented because one of the parties does not agree to its implementation, the juvenile justice process will proceed to juvenile criminal proceedings. In addition, every child in the criminal justice process has the right, among other things, to be free from torture, cruel, inhuman, and degrading treatment or punishment; not to be sentenced to death or life imprisonment; not to be arrested, detained or imprisoned, except as a last resort and for the shortest possible time; or to obtain justice before a juvenile court that is objective, impartial and closed to the public.